Developments in crops and management systems to improve lignocellulosic feedstock production. (9th July 2013) - Coulman, Bruce; Dalai, Ajay; Heaton, Emily; Lee, Camilo Perez; Lefsrud, Mark; Levin, David; Lemaux, Peggy G.; Neale, David; Shoemaker, Sharon P.; Singh, Jaswinder; Smith, Donald L.; Whalen, Joann K.
Abstract There is an urgent need to develop viable, renewable, sustainable energy systems that can reduce global dependence on fossil fuel sources of energy. Biofuels such as ethanol are being utilized as blends in surface transportation fuels and have the potential to improve sustainability and reduce greenhouse gas emissions in the short term. Bioethanol, the most widely used liquid biofuel, is currently produced by converting sugars or starches from feed crops into ethanol. Use of this fuel source displaces and draws water consumption away from agricultural crops, increases soil erosion by shifting land from perennial grasses to annual crops, and increases use of fertilizers and insecticides. In contrast, bioethanol made from lignocellulosic biomass feedstocks does not have these limitations and in addition, offers a larger resource base: the amount of cellulosic material available for potential use vastly outweighs the amount of available starch‐based feedstock. Therefore, bioethanol from lignocellulosic biomass has attracted considerable interest from biofuel developers. This review is an update of some developments to optimize cellulose extraction from feedstock crops and to improve crop yields and logistics. It concludes that agricultural and forestry systems that incorporate lignocellulosic biomass crops can be designed for improved ecological function and energy use efficiency. Development of crops that have both desirable cell‐wall traits and high biomass productivity under sustainable low‐input conditions can significantly enhance the economics and efficiency of the conversion process. Optimizing the logistics of moving feedstock from field or forest to bio‐refinery can significantly reduce costs of using lignocellulosic feedstocks. © 2013 Society of Chemical Industry and John Wiley & Sons, Ltd